Ground Motion Simulations for the 19 January 2020 Jiashi, China, Earthquake Using Stochastic Finite‐Fault Approach. Issue 12 (1st December 2022) - Wang, Chong; Dang, Pengfei; Qi, Wenhao; Li, Yadong; Wang, Fuyun; Bo, Jingshan
Abstract: A 6.0‐magnitude ( M w ) earthquake was reported to have occurred in Jiashi County, Xinjiang at 21:27 on 19 January 2020, Beijing time (13:27 UTC). This study applied a stochastic finite‐fault approach based on the dynamic corner frequency (EXSIM) to simulate 23 near‐field stations within a distance of 120 km from the epicenter. The stochastic finite‐fault approach is the simplest and most effective method for simulating high‐frequency ground motions. According to studies and empirical relationships, we estimated a region‐specific parameter ( κ 0 ) for use in simulations. In this study, two different slip models, namely, random and inverted slip models, were used to explain their influence on the simulation results. For most stations, the simulated seismic characteristics, such as the peak ground acceleration (PGA), pseudo spectral acceleration, and Fourier acceleration spectrum, are highly compatible with the observed values in the frequency range ( f > 1 Hz), indicating that the stochastic finite‐fault approach is not highly sensitive to input slip distributions and fault dimensions. The simulation results indicated no significance between the two slip models under high‐frequency conditions. Finally, based on the predicted PGA values of 1891 field points selected near the fault, the acceleration field of the Jiashi earthquake is plotted. The results show that the use of the acceleration time history predicted by modified EXSIM is feasible and practical in the high‐frequency band above 1 Hz. Key Points: The stochastic finite‐fault method was applied to simulate the near‐field ground motion of the Jiashi, China, earthquake The input parameters were selected and the simulated and observed results were compared The spatial distribution of the simulated peak ground acceleration was predicted